Overexpression of Bcl-2 by activated human hepatic stellate cells: resistance to apoptosis as a mechanism of progressive hepatic fibrogenesis in humans. Issue 8 (19th January 2006) - Novo, E; Marra, F; Zamara, E; Valfrè di Bonzo, L; Monitillo, L; Cannito, S; Petrai, I; Mazzocca, A; Bonacchi, A; De Franco, R S M; Colombatto, S; Autelli, R; et al.
Abstract : Background and aims: Myofibroblast-like cells, originating from activation of hepatic stellate cells (HSC/MFs), play a key role in liver fibrosis, a potentially reversible process that may rely on induction of HSC/MFs apoptosis. While this possibility has been shown in cultured rat HSC, very limited data are currently available for human HSC/MFs. Methods: Cultured human HSC/MFs were exposed to several proapoptotic stimuli, including those known to induce apoptosis in rat HSC/MFs, and induction of cell death and related mechanisms were investigated using morphology, molecular biology, and biochemical techniques. Results: In this study we report that fully activated human HSC/MFs did not undergo spontaneous apoptosis and survived to prolonged serum deprivation, Fas activation, or exposure to nerve growth factor, tumour necrosis factor α (TNF-α), oxidative stress mediators, doxorubicin, and etoposide. Induction of caspase dependent, mitochondria driven apoptosis in HSC/MFs was observed only when protein synthesis or transcription were inhibited. Importantly, the process of HSC activation was accompanied by changes in expression of a set of genes involved in apoptosis control. In particular, activated human HSC/MFs in culture overexpressed Bcl-2. The role of Bcl-2 was crucial as Bcl-2 silenced cells became susceptible to TNF-α induced apoptosis. Finally, Bcl-2 was markedly expressed in HSC/MFs present in liver tissue obtained from patients with hepatitis C virus related cirrhosis. Conclusions: Human activated HSC/MFs are resistant to most proapoptotic stimuli due to Bcl-2 overexpression and this feature may play a key role in the progression of fibrosis in chronic liver diseases.